Desulfurization Activity of Ni/NAC Catalysts Prepared by Ultrasonic-Assisted Impregnation - Gong1, Mengdan; Wang1, Xuejiao; Guo1, Jiaxiu; Liu1, Yongjun; Yin1, Huaqiang (Asian Journal of Chemistry, 2014)
Nickel-loaded activated carbons treated by HNO3 (Ni/NAC) were prepared by ultrasonic-assisted impregnation method and characterized by scanning electron microscopy, X-ray diffraction and X-ray photoelectron spectroscopy. Desulfurization activity of catalysts and the effects of different ultrasonic time on desulfurization activity were studied. The results showed that the catalysts prepared by ultrasonic-assisted impregnation exhibit better desulfurization activity compared to the catalysts prepared by a single impregnation. With the increase of the ultrasonic oscillation time, the desulfurization activity increases firstly and then decreases. The catalyst prepared by 80 min ultrasonic oscillation shows the best desulfurization activity and has sulfur capacity of 235.8 mg/g. Nickel and NiO species coexist in all prepared catalysts, but the ultrasonic oscillation can improve the dispersion of the active components and create the chemisorbed oxygen, resulting in the improvement of desulfurization activity of the catalysts.